Step-by-step: the WTO agriculture negotiations - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
February 2000: draw up proposals for negotiations.March 2001: more technical discussions start on specific topics.November 2001: in Doha, Qatar, the Third Ministerial Conference, drawing on the work of the Agriculture Committee, determines the goals...